Development of representative examples to evaluate specification language functionality characteristics - Gasperovič, Jelena (Lietuvos matematikos rinkinys, 2023)
The paper describes shortly the main principles of representative examples development, provides the essence of the methodology to develop representative examples and an example of its application. The main contribution of the paper is the methodology to develop representative examples that could be used to evaluate the sufficiency of specification language for specification of software system requirements.